Case report: Bilateral posterior ischemic optic neuropathy in a patient with atrial fibrillation and multifocal embolic stroke - Kang, Jin-Ju; Lee, Eun-Su; Lee, Haeng-Jin; Hwang, Seungbae; Chung, Myung-Ja; Oh, Sun-Young (Frontiers in Neurology, 2022)
An 80-year-old female with a history of diabetes mellitus (DM) and hypertension presented with sudden onset of sequential bilateral visual loss. The best visual acuity was light perception in the right eye and finger counting in the left eye, however, bilateral fundus did not reveal optic disc edema. Diffusion-weighted magnetic resonance imaging (MRI) of the brain revealed acute embolic stroke and diffusion restriction in the posterior portion of both optic nerves. The 24-h Holter monitor showed persistent atrial fibrillation (AF) with rapid ventricular response. The presence of painless and severe visual loss at onset unaccompanied by optic disc edema in the patient with newly detected uncontrolled AF and multiple embolic infarctions favored a diagnosis of non-arteritic posterior ischemic optic neuropathy (PION). The current case contributes to better understanding of PION pathophysiology and associated risk factors, indicating a possible relationship between non-arteritic PION and uncontrolled AF and embolic cerebral infarction.